2003
DOI: 10.1097/00126334-200308150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of a New Less Sensitive HIV-1 Enzyme Immunoassay for Use in Estimating HIV Seroincidence

Abstract: Less sensitive (LS) HIV-1 enzyme immunoassays (EIAs) have significantly improved the quantity and quality of HIV surveillance data. The first LS-HIV-1 EIA, the Abbott 3A11-LS, provided reliable incidence data, but the assay required specialized equipment, and the lack of available reagents made testing difficult. This study evaluated the use of an alternate assay, a modified version of the Vironostika HIV-1 EIA (Vironostika-LS), to be used for LS testing. The Vironostika-LS has similar performance characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
127
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 19 publications
1
127
1
2
Order By: Relevance
“…Double-negative samples were considered HIV-1 negative. Samples for which the ELISA results were inconclusive, as well as those testing positive for HIV-1 only once, were further analyzed by Western blot according to the guidelines established by the Brazilian Health Ministry [3].…”
Section: Starhsmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-negative samples were considered HIV-1 negative. Samples for which the ELISA results were inconclusive, as well as those testing positive for HIV-1 only once, were further analyzed by Western blot according to the guidelines established by the Brazilian Health Ministry [3].…”
Section: Starhsmentioning
confidence: 99%
“…The HIV-1 epidemic in Brazil is characterized by the number of reported AIDS cases and the number of HIV-infected pregnant women (and their infected children), as well as HIV-1 sentinel surveillance of certain population groups. In several studies, recent HIV-1 infection has been described using a less sensitive ELISA [1][2][3][4]. This detection strategy, known as the serologic testing algorithm for recent HIV seroconversion (STARHS) [3], has been used to estimate HIV-1 incidence and to investigate epidemiological aspects in newly-infected individuals.…”
mentioning
confidence: 99%
“…The patient was determined to have been recently infected with HIV-1 ( < 6 months) by serological incidence testing. 13 The viral load and CD4 counts over the period of study are shown in Fig. 1.…”
mentioning
confidence: 99%
“…Le indagini di laboratorio finora disponibili per la diagnosi e il monitoraggio dell'infezione da HIV (ricerca di anticorpi con test di "screening" e di conferma, antigene p24, test combinati per anticorpi e antigene (2), HIV-RNA, conta dei linfociti CD4) non si sono rivelate accurate nell'individuare chi, fra i nuovi infetti, fosse anche un sieroconvertito recente. Alcuni studi internazionali hanno analizzato la possibilità di identificare le persone che hanno sieroconvertito recentemente per l'HIV attraverso un test da effettuare su un semplice campione di siero; in particolare, negli Stati Uniti è stato studiato ed applicato il "detuned test" o "STARHS" (Serologic Testing Algorithm for Recent HIV Seroconversion), che tuttavia presenta molti limiti (7,8,11). Una "datazione" dell'infezione, utile sia per scopi epidemiologici (sorveglianza di infezione, incidenza) che clinici è teoricamente possibile, come per altre patologie infettive, con metodiche atte a valutare l'avidità anticorpale, in base We evaluated the accuracy of the avidity index (AI) of anti-HIV antibodies on 357 serum samples obtained from 127 subjects for whom an estimated date of seroconversion was calculated on the basis of the interval between the last negative and first positive anti-HIV test result.The ROC curve analysis performed at different thresholds of the AI showed that a cutoff of 0.80 (93.0% sensitivity and 98.5% specificity) yields the best overall accuracy (95.8%) and should be employed for surveillance purposes, whereas the application of the anti-HIV AI on individual cases is not recommended.…”
unclassified